Implementation of the Pancasila Student Profile on Global Diversity Dimensions in Junior High Schools - Pratiwi, Erma Dyah; Triyanto, Triyanto; Gunawati, Dewi (Journal of Humanities and Social Sciences Studies, 2024)
Globalization challenges national identity with global influences that disregard national borders and internal influences such as ethnic and regional ties. Pancasila is needed as a filter for new values to preserve local culture. This study explores the formation of the Profile of Pancasila Students in the Global Diversity dimension among 7th-grade students at Harapan Bangsa Outstanding Junior High School. This research used a qualitative method with data collection techniques through interviews, observations, and documentation. The research sample consists of 7th-grade students at Harapan Bangsa Outstanding Junior High School. The research instruments included interview guidelines, observation sheets, and related documents. The data analysis technique used was an interactive descriptive analysis by Miles and Huberman, which includes data collection, data reduction, data presentation, and conclusion/verification. The results showed that students can better explore, explain, and understand cultural diversity in Indonesia through active and interactive learning. Civics teachers' strategies in shaping the Profile of Pancasila Students with a Global Diversity dimension include jigsaw learning, Snowball Throwing, quizzes, and Pancasila Profile strengthening projects. The implications of this research contribute to the development of more effective and efficient learning to enhance students' ability to understand cultural diversity in Indonesia.